1991
DOI: 10.1200/jco.1991.9.5.729
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival in patients with poor-prognosis malignant melanoma treated with adjuvant levamisole: a phase III study by the National Cancer Institute of Canada Clinical Trials Group.

Abstract: Five hundred forty-three patients with completely resected malignant melanoma who were considered to have a significant risk of developing recurrent disease were randomized to one of four study groups. One group received levamisole 2.5 mg/kg on 2 consecutive days weekly for 3 years, a second group received bacillus Calmette-Guérin (BCG) for 3 years. A third group alternated 8-week courses of BCG and levamisole for 3 years and a fourth group underwent clinical assessment at the same frequency as the three treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 6 publications
0
24
0
1
Order By: Relevance
“…A fourth, non-placebo-controlled, trial by the NCIC (National Cancer Institute of Canada Clinical Trials Group) compared levamisole vs. levamisole + BCG vs. BCG vs. observation. After 5 years, there was a significant benefit for the 135 patients in the levamisole arm with respect to overall survival (74 % vs. 62 %; p = 0.0268) [373]. Meta-analysis of 5-year survival data from all 4 trials yielded no significant benefit for levamisole in terms of mortality risk (RR 0.94 [95 % CI 0.75-1.20; p = 0.6]) [348].…”
Section: A Pflugfeldermentioning
confidence: 99%
“…A fourth, non-placebo-controlled, trial by the NCIC (National Cancer Institute of Canada Clinical Trials Group) compared levamisole vs. levamisole + BCG vs. BCG vs. observation. After 5 years, there was a significant benefit for the 135 patients in the levamisole arm with respect to overall survival (74 % vs. 62 %; p = 0.0268) [373]. Meta-analysis of 5-year survival data from all 4 trials yielded no significant benefit for levamisole in terms of mortality risk (RR 0.94 [95 % CI 0.75-1.20; p = 0.6]) [348].…”
Section: A Pflugfeldermentioning
confidence: 99%
“…Although the most signif icant prognostic factor if the number of nodal metastases, ulceration and tumor thickness are also significant in most studies. To date, there is no standardized adjuvant treatment after radical surgery [14][15][16], even if the WHO melanoma program has recently published preliminary results of a ran domized adjuvant IFN trial, showing a higher 2-year disease-free interval in patients who were given IFN-a [17].…”
Section: Introductionmentioning
confidence: 99%
“…2 By 1990, 3 major studies supported levamisole as an adjunctive therapy in melanoma 3 and colon cancer. 4 Although levamisole appeared to be nontoxic at single or low doses, long-term use in clinical trials demonstrated that 2.5%-13% of patients developed life-threatening agranulocytosis, and up to 10% of those instances resulted in death.…”
Section: Discussionmentioning
confidence: 99%
“…She was found to have positive perinuclear antineutrophil cytoplasmic antibodies (p-ANCA), antimyeloperoxidase (MPO) antibodies, anticardiolipin (ACL) antibodies, and lupus anticoagulant (LAC). By hospital day 3, her lesions had significantly improved without any intervention, and her absolute neutrophil count increased to 1080/mm 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation